A Randomized Phase II Trial of Pioglitazone for Lung Cancer Chemoprevention in High-Risk Current and Former Smokers - Keith, Robert L.; Blatchford, Patrick J.; Merrick, Daniel T.; Bunn, Paul A.; Bagwell, Brandi; Dwyer-Nield, Lori D.; Jackson, Mary K.; Geraci, Mark W.; Miller, York E. (Cancer prevention research (Philadelphia, Pa.), 2019)
Lung cancer chemoprevention, especially in high-risk former smokers, has great potential to reduce lung cancer incidence and mortality. Thiazolidinediones prevent lung cancer in preclinical studies, and diabetics receiving thiazolidinediones have lower lung cancer rates which led to our double-blind, randomized, phase II placebo-controlled trial of oral pioglitazone in high-risk current or former smokers with sputum cytologic atypia or known endobronchial dysplasia. Bronchoscopy was performed at study entry and after completing 6 months of treatment. Biopsies were histologically scored, and primary endpoint analysis tested worst biopsy scores (Max) between groups; Dysplasia index (DI) and average score (Avg) changes were secondary endpoints. Biopsies also received an inflammation score. The trial accrued 92 subjects (47 pioglitazone, 45 placebo), and 76 completed both bronchoscopies (39 pioglitazone, 37 placebo). Baseline dysplasia was significantly worse for current smokers, and 64% of subjects had mild or greater dysplasia at study entry. Subjects receiving pioglitazone did not exhibit improvement in bronchial dysplasia. Former smokers treated with pioglitazone exhibited a slight improvement in Max, while current smokers exhibited slight worsening. While statistically significant changes in Avg and DI were not observed in the treatment group, former smokers exhibited a slight decrease in both Avg and DI. Negligible Avg and DI changes occurred in current smokers. A trend toward decreased Ki-67 labeling index occurred in former smokers with baseline dysplasia receiving pioglitazone. While pioglitazone did not improve endobronchial histology in this high-risk cohort, specific lesions showed histologic improvement, and further study is needed to better characterize responsive dysplasia.